‘I am not Homophobic But...’: Disclaiming in Discourse Resisting Repeal of Section 28 - Burridge, Joseph (Sexualities, 2004)
This article attempts to take seriously the discourse of the morally conservative in the context of the failed repeal of Section 28 in the year 2000, and explores the operation of opposition to repeal which denied that homophobia was its motivation. It is argued that such disclaiming implies an orientation towards an attribution of homophobia as unhelpful or undesirable in this context. The failure of those advocating repeal to successfully problematize such arguments is deemed to reflect a collective ‘discourse of tolerance’ which assisted the arguments of those against repeal.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; homophobie; hétérosexisme; inégalités; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; section 28; soc2014; sociologie; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Patriarcat (Théorie du) - Delphy, Christine (Dictionnaire critique du féminisme, 2004)
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; féminisme matérialiste; outils; ouvrages de références; patriarcat; premier cycle; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

L’épineuse couronne de la féminité. Féminin, religion et politique au lendemain de 1848. France-Allemagne - Delvallez, Sophie; Primi, Alice (Revue d’histoire du XIXe siècle, 2004)
Keywords: 1800-1899; 1840-1849; allemagne; approches et analyses; cours; discipline; europe; france; his4330; histoire; histoire des femmes*; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; religion; régions géographiques; sciences humaines; thématiques

Dictionnaire critique du féminisme - Hirata, Helena (Presses universitaires de France, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail

Genre et migration internationale Critique du réductionnisme théorique - Kofman, Eléonore (Les cahiers du CEDREF, 2004)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; immigration; inégalités; justice sociale; migration; postmodernisme; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail